2018
DOI: 10.3390/e20030154
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Entropy Characterizes the Gene Expression and Protein-Protein Networks in Four Types of Cancer

Abstract: Abstract:There is an important urgency to detect cancer at early stages to treat it, to improve the patients' lifespans, and even to cure it. In this work, we determined the entropic contributions of genes in cancer networks. We detected sudden changes in entropy values in melanoma, hepatocellular carcinoma, pancreatic cancer, and squamous lung cell carcinoma associated to transitions from healthy controls to cancer. We also identified the most relevant genes involved in carcinogenic process of the four types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Banerji et al [276] suggested that signaling entropy provided a potential measure in cancer by investigating microarray gene expression data in 3668 breast cancer samples and 1692 lung adenocarcinoma samples. Juarez-Flores and José [277] also detected the sudden changes in entropy values in four cancer types and identified the most relevant genes involved in carcinogenic processes that would be potential biomarkers or therapeutic targets. Intriguingly, Teschendorff et al [278] found that increased network entropy of cancer cells would be driven by the scale-free (or near scale-free) property of the interaction network and the positive correlation between differential gene expression and node degree.…”
Section: Network Entropymentioning
confidence: 98%
“…Banerji et al [276] suggested that signaling entropy provided a potential measure in cancer by investigating microarray gene expression data in 3668 breast cancer samples and 1692 lung adenocarcinoma samples. Juarez-Flores and José [277] also detected the sudden changes in entropy values in four cancer types and identified the most relevant genes involved in carcinogenic processes that would be potential biomarkers or therapeutic targets. Intriguingly, Teschendorff et al [278] found that increased network entropy of cancer cells would be driven by the scale-free (or near scale-free) property of the interaction network and the positive correlation between differential gene expression and node degree.…”
Section: Network Entropymentioning
confidence: 98%
“…There are different metrics that can be obtained from networks as the hubs which are commonly referred as the most connected nodes which lead to network instability if they are perturbed 10 13 . Besides, other network measures as betweenness and multivariate entropy have been used to analyze cancer networks to find putative potential targets for cancer disease 14 , 15 . We previously identified a set of nodes which due to its biological and network properties we called them network gatekeepers 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the area of biology, they have been used to analyze a population's structure [2,3], and pandemics [4,5]. The use of protein-protein interaction networks coupled with information theory have led to discover potential therapeutic biomarkers on cancer research [6]. Integrative approaches for anticipating critical transitions have been proposed [7] in several phenomena, although the area of cardiology has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%